Beyond Fake News: The Rise of Deepfakes and the Crisis of Epistemic Trust in Digital Journalism - Prasojo Prasojo; Ishara Ratnayake; Kumudu Wijerathna (Yayasan Adra Karima Hubbi, 2026)
Background. The rapid advancement of artificial intelligence has transformed the digital information landscape, enabling the creation of highly realistic synthetic media known as deepfakes. Unlike conventional fake news, deepfakes possess the capacity to manipulate audiovisual evidence in ways that challenge public perceptions of authenticity and truth. The growing proliferation of deepfake content has raised significant concerns regarding the credibility of digital journalism, the reliability of information sources, and the erosion of epistemic trust within contemporary communication environments. Purpose. This study aims to examine how the rise of deepfakes contributes to the crisis of epistemic trust in digital journalism and to explore the broader implications of synthetic media for journalistic credibility and public knowledge. Method. A qualitative research design based on a critical literature review and thematic content analysis was employed. Data were collected from peer-reviewed journal articles, institutional reports, policy documents, and documented case studies published between 2018 and 2025. Results. Findings reveal that deepfakes undermine trust not only by disseminating deceptive content but also by fostering uncertainty regarding the authenticity of legitimate information. Authenticity ambiguity, verification challenges, audience skepticism, and institutional trust erosion emerged as the dominant themes across the analyzed literature. Conclusion. The study concludes that deepfakes represent a fundamental epistemic challenge that extends beyond misinformation. Preserving trust in digital information ecosystems requires integrated responses involving technological innovation, journalistic verification, media literacy, and governance frameworks.